Study the effect of Ag nanoparticles and ZnO nanoparticles at different concentrations on the viscosity and surface tension of Polyacrylamide solutions - Najla Ali Elgheryani (Iraqi Journal of Physics, 2019)
Polyacrylamide Solutions of different concentrations (0.2, 0.4, 0.6, 0.8, 1.0 %) of Ag nanoparticles and ZnO nanoparticles were prepared, the viscosities and surface tension were measured for all solutions, where measurements indicated an increase in these properties with increased concentration, where the relative viscosity of polyacrylamide/zinc nanoparticles increased from 1.275 to 2.243, and the relative viscosity of polyacrylamide/silver nanoparticles increased from 1.178 to 1.934. Viscosity is significant parameters during electrospinning process. While the surface tension of the polyacrylamide/zinc nanoparticles has changed from 0.0343 Nm-1 to .0.0.0 Nm-1 and changed from .0.000Nm-1 to.0.0.0 Nm-1. Also the constants KH and KK were calculated from the slopes of viscosity figures related to equations of Huggins and Kramer. These results can be used in medical, industrial applications and Scientific studies.